2011
DOI: 10.1163/157180611x592923
|View full text |Cite
|
Sign up to set email alerts
|

Relational Construal in Negotiation: Propositions and Examples from Latin and Anglo Cultures1

Abstract: In certain cultures, relationships are the reason for negotiation. In this article, we offer a rationale regarding why relationships have more or less salience across cultures. We present psychological, economic and sociological factors that explain the reasons for negotiating relationally. Propositions are made as to how cultural construal about relationships influences offers, targets and limits, negotiation strategy and, ultimately, economic and relational outcomes. Our major explanatory construct is new: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…We used a sampling check to demonstrate that the participants had cultural values consistent with those characteristic of their cultures (Lytle, Brett, Barsness, Tinsley, & Janssens, 1995). Specifically, we sought to verify that our Taiwanese participants construed the self as more interdependent than independent and that our U.S. participants construed the self as more independent than interdependent (Markus & Kitayama, 1991;Ramirez-Marin & Brett, 2011), using within-culture t tests to account for the fact that mean responses across groups are potentially biased by response sets (Gelfand, Raver, & Holcombe-Erhart, 2002). Results revealed that in Taiwan, participants had stronger interdependent than independent self-construals, M interdependent self-construal ϭ 3.75, SD ϭ 0.30, ␣ ϭ .60; M ϭ independent self-construal ϭ 3.48, SD ϭ 0.36, ␣ ϭ .64; t(85) ϭ 5.89; p Ͻ .001, whereas U.S. participants had stronger independent than interdependent self-construals, M independent selfconstrual ϭ 4.99, SD ϭ 0.53, ␣ ϭ .65; M interdependent self-construal ϭ 4.73, SD ϭ 0.58, ␣ ϭ .72; t(78) ϭ Ϫ3.09, p Ͻ .001.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a sampling check to demonstrate that the participants had cultural values consistent with those characteristic of their cultures (Lytle, Brett, Barsness, Tinsley, & Janssens, 1995). Specifically, we sought to verify that our Taiwanese participants construed the self as more interdependent than independent and that our U.S. participants construed the self as more independent than interdependent (Markus & Kitayama, 1991;Ramirez-Marin & Brett, 2011), using within-culture t tests to account for the fact that mean responses across groups are potentially biased by response sets (Gelfand, Raver, & Holcombe-Erhart, 2002). Results revealed that in Taiwan, participants had stronger interdependent than independent self-construals, M interdependent self-construal ϭ 3.75, SD ϭ 0.30, ␣ ϭ .60; M ϭ independent self-construal ϭ 3.48, SD ϭ 0.36, ␣ ϭ .64; t(85) ϭ 5.89; p Ͻ .001, whereas U.S. participants had stronger independent than interdependent self-construals, M independent selfconstrual ϭ 4.99, SD ϭ 0.53, ␣ ϭ .65; M interdependent self-construal ϭ 4.73, SD ϭ 0.58, ␣ ϭ .72; t(78) ϭ Ϫ3.09, p Ͻ .001.…”
Section: Methodsmentioning
confidence: 99%
“…Research has long shown that different cultures make different social norms chronically salient. In particular, because members of collectivistic, East Asian cultures construe the self and others as interdependent (Markus & Kitayama, 1991;Ramirez-Marin & Brett, 2011), group harmony is an omnipresent and critically important norm (Leung, 1997). In negotiations specifically, the prospect of upsetting an immediate or longer term relationship with a particular individual strongly favors norms of harmony, discouraging open confrontation (Leung, 1997).…”
Section: Negotiating Teams Across Culturesmentioning
confidence: 99%
“…Having an independent self‐construal means seeing oneself as an autonomous and agentic entity. An interdependent self‐construal, on the other hand, can take two distinct forms: relational and collective (Brewer and Gardner ; Brewer and Chen ; Ramirez‐Marin and Brett ; Lee et al. ).…”
Section: Cultural Background: Social Relationships In China Japan Amentioning
confidence: 99%
“…Having an independent self-construal means seeing oneself as an autonomous and agentic entity. An interdependent self-construal, on the other hand, can take two distinct forms: relational and collective (Brewer and Gardner 1996;Brewer and Chen 2007;Ramirez-Marin and Brett 2011;Lee et al 2012). A relational self-construal refers to the extent to which people regard themselves as connected to other individuals in dyadic relationships; a collective self-construal refers to the self in relation to a group or collective.…”
mentioning
confidence: 99%
“…Having an independent self-construal means seeing oneself as an autonomous and agentic entity. An interdependent self-construal, on the other hand, can take two distinct forms: relational and collective (Brewer and Gardner 1996;Brewer and Chen 2007;Ramirez-Marin and Brett 2011;Lee et al 2012). A relational self-construal refers to the extent to which people regard themselves as connected to other individuals in dyadic relationships; a collective selfconstrual refers to the self in relation to a group or collective.…”
Section: Cultural Background: Social Relationships In China Japan Amentioning
confidence: 99%